Disclosure Strategy and Consumer Perception: The Impact of Managerial Myopia on Firm Value - Wahida, Visda Fitri; Hanafiah, Yasmina Diani (Journal of Economic and Leadership, 2024)
This study examines the relationship between disclosure strategy and consumer perception and the implications of managerial myopia on firm value. In a context where CEOs tend to focus on short-term results, voluntary consumer-friendly disclosure can increase customer trust and satisfaction, which contributes to firm profitability. Although managerial myopia is often considered detrimental, this study shows that short-term-oriented CEO actions can create long-term value through more transparent disclosure and better interaction with consumers. This literature review also highlights the importance of manager compensation design in determining short-term or long-term orientation, and its impact on disclosure decisions. The results show that effective disclosure can reduce market uncertainty, increase consumer loyalty, and ultimately support the growth of firm value. This study concludes that companies should develop a balanced disclosure strategy to achieve long-term success and maintain positive relationships with consumers.